ACCOUNTABILITY OF PERFORMANCE INTEGRATED WITH THE VALUE OF ISLAMIC CIVILIZATION: THE CASE OF MUHAMMADIYAH UNIVERSITY OF MAKASSAR - Rayyani, Wa Ode; Abbas, Ahmad; Hannani, Hannani (Universitas Ahmad Dahlan, 2019)
The objective of this research is to describe accountability of performance integrated with the value of Islamic civilization and find the essence from framework of Islamic accountability of organization. This research is qualitative type using interpretive spiritualism paradigm under ethnomethodology approach. The object of this research is Muhammadiyah University of Makassar and informants are people involved in making a decision in the university. The result reveals that the accountability in Muhammadiyah University of Makassar is built using the religious spiritualism under a foundation of Islamic values consisting of ukhuwah and sincerity, amanah, oriented goal, effectiveness and efficiency, opennes, and consistency. The further result discloses that sincerity is the strongest value to build the accountability of performance